A Pre-service English Teacher’s Emotional Experiences within Teaching Practicum during COVID-19 Pandemic - Egi Rahmawati; Fauzi Miftakh; Abdul Kodir Al-Baekani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
Research has revealed that pre-service teachers at the start of the practicum frequently experience excitement and nervousness, shock and embarrassment once they begin teaching, and guilt and regret somewhere at completion of the practicum (Zhu, 2017). Based on this problem, the study aims to explore the emotions of a male EFL pre-service teacher when undergoing English teaching practicum during COVID-19 outbreak in Indonesian academic settings and the strategies used to cope with such emotional challenges. The data were derived from interviews and diary entries and were then transcribed, arranged based on needs, and analyzed thematically using the “Emotional Geography” framework (Hargreaves, 2001a) which focusing on five emotional dimensions: physical, moral, socio-cultural, professional and political. Research findings indicate that during teaching practicum activities affected by COVID-19, the participant experienced such negative feelings such as nervousness, fear, anxiety, shock, confusion, clueless, stress, overwhelmed Ness, and powerless. However, the pre-service teacher also felt positive feelings such as compassion, happiness, relaxedness, calmness, gratitude and enjoyment after building close bonds with the community members. By this study, the researchers hope to provide broader insights and practical benefits for teachers and pre-service English teachers’ development in which they can take advantage of current research results to find out what feelings might be faced in implementing English teaching practicum and what strategies can be developed and implemented to overcome these emotional problems.